GANTI RUGI DALAM ASURANSI KECELAKAAN PENUMPANG ANGKUTAN UDARA KOMERSIAL - Lina Gustiari, Luh Gde; Suarbha, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
This writing shall be entitled as “Damages in Commercial Flight AccidentsInsurance for Passengers”. This writing shall apply normative legal research methodby analyzing primary and secondary sources of data. Thus, this writing shall illustratethe effective period and the termination of risk during the aviation services, and theamount of damages compensated by passengers in the circumstances of the accidentoccurred. Risk occurred the moment passenger aboard the aircraft, flight, and end ofthe flight. Amount of damages compensated ranged from IDR 50,000,000.00; forinjured passengers due to aircraft accident, IDR. 25,000,000.00; for passengers whoexperienced disabledness due to the accident.
Keywords: Damages, Insurance, Flight, Commercial